Kidney cell culture of Rana dybowskii and study molecules of TRIF in Rana dybowskii cells under the stress of Aeromonas hydrophila - B. Wang; J. Shao; L. Qu; Q. Xu; D. Zheng (The European Zoological Journal, 2023)
AbstractAs a model organism, the cell culture method of Rana dybowskii (Rd) has not received widespread attention. We obtained kidney cells from Rana dybowskii by tissue block culture and enzyme digestion, and optimized the culture method by changing different culture conditions. We can more conveniently study the operation of the Rana dybowskii immune system through cell lines. One of the most important adaptor proteins in the Toll-like receptors (TLRs) signaling pathway, TIR-domain-containing adaptor inducing interferon-β (TRIF), plays a role in the apoptosis pathway and participates in the ubiquitin-mediated protein hydrolysis pathway. This rationalizes the significance of TRIF in the immune cascade signaling pathway. To obtain and analyze the full-length sequence of cDNA, sequential structures of amino acids, as well as Rana dybowskii TRIF expression profiles, the present work carried out multiple-sequence alignment, rapid amplification of cDNA ends (RACE), the establishment of a phylogenetic tree, search for the conserved domain, and qRT-PCR. Results revealed 1733-bp full-length cDNA of RdTRIF with an open reading frame (ORF) of 1281 bp, which encoded one protein containing 426 amino acid residues. The amino acid sequence of RdTRIF confirmed the presence of one Toll/interleukin-1 receptor (TIR) domain. As a kind of hydrophilic protein, the pI and molecular weight of RdTRIF were 5.67 and 24.76 kDa, respectively. We predicted 51 candidate phosphorylation sites, including 32 serine residues, 16 threonine residues along with 3 tyrosine residues. The phylogenetic tree and multiple-sequence alignment substantiated the highest homology of RdTRIF protein to Xenopus tropicalis homologs. According to the qRT-PCR results, the expression of RdTRIF was noted under the stress of Ah in the kidney.